The reconfiguration of social, digital and physical presence: From online church to church online - Cooper, Anthony-Paul (HTS teologiese studies, 2021)
Digital presence refers to technologies that provide communities a shared experience and a sense of togetherness, despite geographical distance. Emerging technologies for digital presence provide the church with both theological questions (e.g. related to the validity of sacraments when administered online) and practical opportunities. Think of the pros and cons for online communion in some churches: is digital presence real presence? The digital realm as a thread of the universe leads to rethinking of the church as a social, digital and physical unity. What kind of new possibilities could digital presence in digital realities provide to spiritual experience, individually and within the worship?Contribution: Rather than a plain application of the existing technologies to digitise the current functions and events of congregations for online services, technology should expand and reform the church online. This study aims to discuss the transformation from online church to church online. The technical solution for digital presence was inspired by the demands of a Finnish plug-in campus in an African setting, which draws inspiration from African concepts of community and place.